“Indigenous” Cooperatives Supporting SDGs Development in Indigenous Communities: a study of social and communication (Case: The Consumer Cooperative of Warga Sauyunan, Kampung Naga, Regency of Tasikmalaya, West Java, Indonesia) - Wawan Lulus Setiawan; Kikin Hidayatullah; Nurul Azizah; Fadya Prayusinar (Research Collaboration Community (RCC), 2023)
The purpose of this study is to describe the role of cooperative, namely The Consumer cooperative of Warga Sauyunan, in supporting SDGs development in indegenous community at Kampung Naga, The Regency of Tasikmalaya, West Java, Indonesia. The kampong consists of 101 house-hold and 300 people. This study was based on the background of poverty issues as the main problem faced in Indonesian socio-economy, especially in rural areas, and the issue of sustainability of community development. Cooperative development program could be seen as one effort to reduce poverty through community based development (CBD) by paying attention to the SDGs principles . This study used desciptive method. This research resulted in some findings: (1) cooperative could support the indegenous community in Kampung Naga by promoting their economy, and by strengthening social ties and network in the communities, (2) cooperative practice and principles are in line with the social values and princples of the community in which they always keep the harmonious relationship with the nature, (3) indegenous communication pattern of the community is the local wisdom which support cooperative development in indegenous community and SDGs principle. This research has implications for policies of developing the cooperative development program for other indegenous communities in Indonesia. It also has implication on the adoption of cooperative concept and principles by indegenous people as a new mind-set for more productive, valuable and sustainable development.